Phase 2 study of subcutaneous omacetaxine mepesuccinate after TKI failure in patients with chronic-phase CML with T315I mutation - Cortes, Jorge (Blood, 2012)
Chronic myeloid leukemia (CML) patients with the BCR-ABL T315I mutation do not benefit from therapy with currently approved tyrosine kinase inhibitors. Omacetaxine mepesuccinate is a protein synthesis inhibitor that has demonstrated activity in cells harboring the T315I mutation. This phase 2 trial assessed the efficacy of omacetaxine in CML patients with T315I and tyrosine kinase inhibitor failure. Patients received subcutaneous omacetaxine 1.25 mg/m(2) twice daily, days 1-14, every 28 days until hematologic response or a maximum of 6 cycles, and then days 1-7 every 28 days as maintenance. Results for patients treated in chronic phase are reported here. Patients (n = 62) received a median of 7 (range, 1-41) cycles. Complete hematologic response was achieved in 48 patients (77%; 95% lower confidence limit, 65%); median response duration was 9.1 months. Fourteen patients (23%; 95% lower confidence limit, 13%) achieved major cytogenetic response, including complete cytogenetic response in 10 (16%). Median progression free-survival was 7.7 months. Grade 3/4 hematologic toxicity included thrombocytopenia (76%), neutropenia (44%), and anemia (39%) and was typically manageable by dose reduction. Nonhematologic adverse events were mostly grade 1/2 and included infection (42%), diarrhea (40%), and nausea (34%). Omacetaxine may provide a safe and effective treatment for CML patients with T315I mutation. This study is registered at www.clinicaltrials.gov as NCT00375219.